Kajian Perilaku Beruang Madu (Helarctos malayanus) di Kandang Transit Balai Konservasi Sumber Daya Alam Kalimantan Tengah - Yani Suryani; Nurul Aulia Fitri; Ettie Tatiana; Opik Taupiqurrohman (Gunung Djati Conference Series, 2021)
Sun Bear (Helarctos malayanus) is a type of bear lives in tropical rain forests, Southeast Asia. In Indonesia, the distribution of the Sun Bear is found on the islands of Kalimantan and Sumatra. Sun Bears are solitary animals and are rarely found in groups. Over time, the population of Sun Bears is decreasing due to habitat destruction and poaching. For this reason, research is needed on the behavior of Sun Bears as one of the efforts in its preservation. Daily behavior that can be found in Sun Bears can be in the form of foraging and feeding, grooming, locomotion, and resting behavior. This study aims to determine the behavior of Sun Bears in transit cages at the Natural Resources Conservation Agency (BKSDA) Central Kalimantan. The method used in this research is a descriptive method with a sampling technique in the form of Focal Animal Sampling. Data collection is carried out in January-February 2021, every day, Monday-Friday at 10.00 WIB and 15.30 WIB and Saturday-Sunday at 09.00-12.30 WIB. Based on the observations, data on the behavior of Sun Bears were obtained which include feeding, grooming, locomotion and playing objects, vocalizations, defecating and urinating, and resting. Based on the behavioral data obtained, the highest percentage of 58% is in locomotion behavior and playing objects. Then, the next highest percentage is 15% on grooming behavior, 14% on feeding behavior, 10% on resting behavior, 2% on defecation and urination behavior, and the lowest percentage is on vocalization behavior which is 1%.